FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN SASARAN KESELAMATAN PASIEN DI RUANG RAWAT INAP RSUD TELUK KUANTAN - FITRA MAYENTI; DILGU MERI; PAPAT CAHYADI; SUCI AMIN (Jurnal Ilmu Keperawatan, 2021)
Patient safety is a very serious global health problem. In recent years, countries have realized the importance of patient safety. The application of patient safety management in the hospital plays a very important role in preventing or minimizing adverse patient safety incidents. The purpose of this study was to determine the factors associated with the implementation of patient safety in Inpatient Rooms at Teluk Kuantan Hospital. This type of research was quantitative with a correlation design. The study was conducted from December 2020 to March 2021. The population in this study were nurses in the Inpatient Room with a total sample of 49 people who were taken using Disproportionate stratified random sampling. The results of this study found that the majority of the nurse's knowledge level was in the good category, namely 24 people (49.0%), the majority of the respondents 'attitudes were in the good category, namely 24 people (49.0%), the majority of the respondents' education level was intermediate, namely 36 people (73.5%), the majority of patient safety facilities were in the adequate category, namely as many as 33 people (67.3%) and the majority of the application of patient safety targets in the good category, namely 24 people (49.0%). There is a relationship between the level of knowledge (p value 0.000), attitude (p value 0.009), education (p value 0.034) and facilities and infrastructure (p value 0.000) with the application of patient safety goals in inpatient room nurses at Teluk Kuantan Hospital. It is suggested to Teluk Kuantan Regional Hospital to motivate nurses to improve their education to a higher level so that the implementation of patient safety targets can be carried out well and provide socialization to all parties to better understand the patient safety target indicators.